Two new species of Leptobrachella Smith 1925 (Amphibia: Megophryidae) from Cao Bang Province, Vietnam - Luong, Anh Mai; Hoang, Chung Van; Pham, Cuong The; Ziegler, Thomas; Nguyen, Truong Quang (Zootaxa, 2023)
Two new species, Leptobrachella phiaoacensis sp. nov. and Leptobrachella phiadenensis sp. nov., are described from Phia Oac-Phia Den National Park, Cao Bang Province, Vietnam based on genetic divergence and morphological differences. Leptobrachella phiaoacensis sp. nov. is characterized by a combination of the following characters: size medium (27.8–33.3 mm in five adult males and 31.5–41.8 mm in five adult females); head longer than wide; tympanum distinct; dorsal skin shagreened with fine tubercles; toes webbing rudimentary, with narrow lateral fringes; supratympanic fold edged by a distinct black line; the presence of a dark brown triangle in interorbital region and a W-shaped marking in scapular region; belly from pinkish white to white with dark brown specking on belly periphery; iris bicolored copper in upper part, fading to silvery grey in lower part. Leptobrachella phiadenensis sp. nov. is distinguished from its congeners by a combination of the following morphological characters: size medium (27.6–28.6 mm in two adult females); head wider than long; tympanum distinct; skin on dorsal head and body rough with warts, tubercles and dermal ridges; toes webbing rudimentary, with narrow dermal fringes; supratympanic fold orange; dorsal surface of head and body with some large dark brown markings, a dark brown triangle in interorbital region, edged in white; flank light brown with some dark flecks; belly white with dark specking on outer margins; iris bicolored, copper in upper part, fading to silvery grey in lower part. In terms of genetic distance, the two new species differ from each other and other congeners for which comparable sequences are available by at least 3.7% (16S rRNA gene). Recognition of these new species brings the total number of known species in the genus Leptobrachella from Vietnam to 34.